Legal Protection for Notaries in Reporting Money Laundering Crimes Using the Whistleblower Protection Model in Indonesia - Ali Abdullah; Suhendar; Rini Meliana; Muhammad Sirajuddin Qahtan Hamdan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The notary profession, as a public official authorized to create authentic deeds, is often vulnerable to money laundering cases due to the complexity of client transactions that cannot be fully verified. This study aims to analyze the concept of legal protection for notaries in money laundering cases and optimize the role of whistleblower protection as an effective protection instrument. The research method uses a normative juridical approach with an analysis of laws and regulations, court decisions, and comparative studies of protection systems in other countries. The results show that existing legal protection mechanisms, such as the approval of the Regional Notary Honorary Council (MKNW) and the Witness and Victim Protection Law, are still weak because they are procedural and unresponsive to the complexity of money laundering cases. Notaries face a dilemma between the obligation to report suspicious transactions and the principle of client confidentiality, plus the application of the burdensome principle of reverse burden of proof. Optimizing whistleblower protection requires the reconstruction of a comprehensive legal framework through regulatory amendments, including the Criminal Procedure Code (KUHAP) and other regulations to provide protection for notaries. This can be done by establishing a Legal Profession Protection Agency, developing special reporting protocols, and an inter-institutional integration system. The ideal protection model should provide legal immunity for whistleblowers in good faith, guarantee identity confidentiality, and a compensation mechanism for notaries who suffer losses due to the implementation of professional obligations.